The impact of wheat market liberalization on the seed industry's innovative capacity: an assessment of Brazil's experience - Larissa Flister; Viktoriya Galushko (Agricultural and Food Economics, 2016)
Market liberalization has a profound impact on the structure of economies as well as changes the roles of the public and private sectors and affects innovative capacity of countries. This paper explores the Brazilian experience with wheat market liberalization and the impact on the seed sector. The analysis presented in this paper is based on interviews with 12 experts intimately involved in wheat research and breeding in Brazil. The analysis reveals liberalization boosted private investment in wheat R&D, which translated into increased research output. However, Brazil faced many challenges in establishing wheat innovation system and important lessons can be drawn from its experience.
Keywords: 330; Wheat; Market liberalization; Innovation; Private R&D; Qualitative analysis